Medical Imaging Compatibility of Magnesium- and Iron-Based Bioresorbable Flow Diverters - Oliver, A.A.; Koons, E.K.; Trester, P.S.; Kleinow, J.E.; Jonsgaard, R.S.; Vercnocke, A.J.; Bilgin, C.; Kadirvel, R.; Leng, S.; Lu, A.; Dragomir-Daescu, D.; Kallmes, D.F. (American Journal of Neuroradiology, 2023)
BACKGROUND AND PURPOSE: Bioresorbable flow diverters are under development to mitigate complications associated with conventional flow-diverter technology. One proposed advantage is the ability to reduce metal-induced artifacts in follow-up medical imaging. In the current work, the medical imaging compatibility of magnesium- and iron-based bioresorbable flow diverters is assessed relative to an FDA-approved control in phantom models.MATERIALS AND METHODS: Bioresorbable flow diverters, primarily composed of braided magnesium or antiferromagnetic iron alloy wires, were compared with an FDA-approved control flow diverter. The devices were assessed for MR imaging safety in terms of magnetically induced force and radiofrequency heating using 1.5T, 3T, and 7T field strength clinical scanners. The devices were deployed in phantom models, and metal-induced image artifacts were assessed in the 3 MR imaging scanners and a clinical CT scanner following clinical scan protocols; device visibility was assessed under fluoroscopy.RESULTS: The magnesium-based bioresorbable flow diverter, iron-based bioresorbable flow diverter, and the control device all demonstrated MR imaging safety in terms of magnetically induced force and radiofrequency heating at all 3 field strengths. The bioresorbable flow diverters did not elicit excessive MR imaging artifacts at any field strength relative to the control. Furthermore, the bioresorbable flow diverters appeared to reduce blooming artifacts in CT relative to the control. The iron-based bioresorbable flow diverter and control device were visible under standard fluoroscopy.CONCLUSIONS: We have demonstrated the baseline medical imaging compatibility of magnesium and antiferromagnetic iron alloy bioresorbable flow diverters. Future work will evaluate the medical imaging characteristics of the bioresorbable flow diverters in large-animal models.BRFDbioresorbable flow diverterFDflow-diverting deviceFeBRFDiron-based bioresorbable flow diverterMgBRFDmagnesium-based bioresorbable flow diverterRFradiofrequencyTggravitational torqueTmaxmaximum torque